Prognostic impact of coronary microvascular dysfunction assessed by caIMR in overweight with chronic coronary syndrome patients - Feng, Cailin; Abdu, Fuad A.; Mohammed, Abdul-Quddus; Zhang, Wen; Liu, Lu; Yin, Guoqing; Feng, Yundi; Mohammed, Ayman A.; Mareai, Redhwan M.; Lv, Xian; Shi, Tingting; Xu, Yawei; et al. (Frontiers in Endocrinology, 2022)
Objective Coronary microvascular dysfunction (CMD) may associate with adverse cardiovascular events in obese patients. Coronary angiography-derived index of microcirculatory resistance (caIMR) is proposed as a less-invasive and pressure-wire-free index to assess CMD. We aimed to investigate the impact of coronary microvascular function assessed by caIMR in patients with overweight and chronic coronary syndrome (CCS). Methods CCS patients who underwent coronary angiography between 2015 to 2018 were included. Overweight was defined as BMI≥24.0kg/m². Impaired coronary microvascular function was defined as caIMR≥25U. The patients were classified according to BMI and caIMR. The primary endpoint was major adverse cardiac events (MACE). Kaplan-Meier and Cox regression analyses evaluated the association between caIMR and MACE. Results Two hundred and eighty-two CCS patients were enrolled. Among these, 169 (59.93%) were overweight. Impaired coronary microvascular function was higher in overweight patients than in patients with normal weight (49.70% vs. 38.05%; P=0.035). During 35 months of follow-up, 33 MACE had occurred. Among the total CCS population, MACE was higher in patients with high caIMR than in low caIMR (18.11% vs. 6.45%, P=0.003). In subgroups analysis, MACE was higher in overweight patients with high caIMR than low caIMR (20.24% vs. 7.06%, P=0.014), while there were no significant differences in normal-weight patients. Multivariate Cox analysis demonstrated that caIMR≥25 was independently associated with MACE in overweight patients (HR, 2.87; 95% CI, 1.12-7.30; P=0.027) but not in the normal-weight patients. In addition, caIMR showed a significant predictive value for adverse outcomes in overweight patients and provided an incremental prediction when added to a prediction model with BMI. Conclusions Impaired coronary microvascular function assessed by caIMR was common and is an independent predictor of MACE in overweight patients with CCS.